Correction: Hereditary gynecological cancer management in women with Lynch syndrome: a survey across Europe - Kevin J. J. Kwinten; Joanne A. de Hullu; Helen Bolton; Monique M. A. Brood-van Zanten; Valentina Chiappa; Stefan Cosyns; Sergi Fernandez-Gonzalez; Angelique Flöter Rådestad; Sophie Frank; Rieke Gellner; Susanne Housmans; Nina Kovacevic; et al. (Familial Cancer, 2026)

Hereditary gynecological cancer management in women with Lynch syndrome: a survey across Europe - Kevin J. J. Kwinten; Joanne A. de Hullu; Helen Bolton; Monique M. A. Brood-van Zanten; Valentina Chiappa; Stefan Cosyns; Sergi Fernandez-Gonzalez; Angelique Flöter Rådestad; Sophie Frank; Rieke Gellner; Susanna Housmans; Nina Kovacevic; et al. (Familial Cancer, 2026)
We aim to compare clinical practices in the gynecological management of women with Lynch syndrome across Europe and assess the need for multidisciplinary gynecological care for this high-risk population. European gynecologists involved in the clinical care of women with Lynch syndrome were invited to complete a cross-sectional survey regarding their clinical practices and organization of care. All participating gynecologists were based in hospitals that are members of the European Reference Network on Genetic Tumour Risk Syndromes (ERN GENTURIS). A total of 33 gynecologists (57%) from 25 unique hospitals across 12 countries participated in the survey. National guidelines on the gynecological management of women with Lynch syndrome were absent in a significant number of European countries. Local multidisciplinary team meetings were available in 61% of hospitals. Considerable heterogeneity was reported in the organization of care, as well as in surveillance, prevention, and treatment strategies. Standardized European guidelines for the gynecological care of women with Lynch syndrome are warranted to promote uniformity. Gynecologists specialized in hereditary cancer should take the lead in developing and implementing these guidelines. Hospitals managing women with Lynch syndrome should have the resources to organize multidisciplinary team meetings, which are crucial for the effective implementation of these guidelines and the improvement of personalized care.